Apple iPad use as a portable instructor operating station for training devices - Emmanuele, C.; Guglielmo, C.; Misani, D.; Parnisari, G. (My University, 2014)
LiOS is a compact, user-friendly instructor station for any kind of flight simulator, ranging from procedural trainers to full mission simulators, which aims to improve the quality of training and reduce its costs by immediately providing essentials information and controls; with LiOS the instructor is less dependent by a fixed workstation allowing a more direct training just by sitting aside the pilot.